Pengaruh Work-Family Conflict, Stres Kerja dan Social Support terhadap Kepuasan Kerja: Studi Kasus pada Guru Wanita di Tangerang - Didi Sutardi; Dewiana Novitasari; Masduki Asbari; Nelson Silitonga; Yunianto Agung Nugroho; Dhaniel Hutagalung; Mustofa Mustofa; Gusli Chidir; Sucipto Basuki; Teguh Yuwono (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aimed to measure the effect of work-family conflict, job stress and social support (supervisor, peer and family support) on job satisfaction of the woman teachers of two private schools in Banten. Data collection was done by simple random sampling to 145 population of woman teachers. The returned and valid questionnaire results were 139 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that work-family conflict, peer support and family support have significant effect on job satisfaction. Meanwhile, job stress and supervisor sopport have not significant effect on job satisfaction. This new research proposed a model for building job satisfaction among the private school teachers in Tangerang through enhancing social support and manage job stress and work-family conflict. This research could pave the way to improve woman teacher readiness in facing the era of education 4.0.